Olivera, Tanzi, Milošević: Why Was Avramović’s Programme Adopted? - Popović, Dejan (Panoeconomicus, 2022)
It was under the UN sanctions during 1992 and 1993 that hyperinflation hit the FRY. Its leadership believed that the fiscal deficit could be covered by printing money, but such a practice resulted in acceleration of hyperinflation. Former World Bank economist Dragoslav Avramović understood that stopping printing money should represent the core of his Programme. He was aware of the Olivera-Tanzi effect, but the fierce attacks on the Programme in the course of its presentation to the nation’s top leadership indicated that those people were not – despite the fact that the real value of all collected taxes decreased to only several tens of millions of US dollars. It was ultimately Milošević himself who decided that the Programme should be approved. The economic problems of the FRY ran much deeper. The involved interests of the nomenklatura in the real sector blocked further reforms and Avramović was dismissed in 1996. Keywords: Hyperinflation, Olivera-Tanzi effect, Inflation tax, Stopping money printing, Money illusion. JEL: E31.